A Switchable Mid‐Infrared Plasmonic Perfect Absorber with Multispectral Thermal Imaging Capability. (14th July 2015) - Tittl, Andreas; Michel, Ann‐Katrin U.; Schäferling, Martin; Yin, Xinghui; Gholipour, Behrad; Cui, Long; Wuttig, Matthias; Taubner, Thomas; Neubrech, Frank; Giessen, Harald
<x xml:space="preserve">Abstract</x> A switchable perfect absorber with multispectral thermal imaging capability is presented. Aluminum nanoantenna arrays above a germanium antimony telluride (GST) spacer layer and aluminum mirror provide efficient wavelength‐tunable absorption in the mid‐infrared. Utilizing the amorphous‐to‐crystalline phase transition in GST, this device offers switchable absorption with strong reflectance contrast at resonance and large phase‐change‐induced spectral shifts.